If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+19=2(x+13)
We move all terms to the left:
x+19-(2(x+13))=0
We calculate terms in parentheses: -(2(x+13)), so:We get rid of parentheses
2(x+13)
We multiply parentheses
2x+26
Back to the equation:
-(2x+26)
x-2x-26+19=0
We add all the numbers together, and all the variables
-1x-7=0
We move all terms containing x to the left, all other terms to the right
-x=7
x=7/-1
x=-7
| n-76=121 | | n-76=21 | | 5x+7(-2-3)=-120 | | 100=4m | | -2.4x=8.5 | | 17-5r+9r=-12+8r-1 | | 3x-5(x+1)=-5-2x | | 7y+20+3y=180 | | 10=j-8 | | (15x+8)°=(21x-10)° | | 7=5+-b | | 0=-16t2+24t+6. | | 9q+6=4q-14 | | 12.8=m-3.8 | | (2x+6)+5x=8x-11 | | (6x-9)=4x+12 | | 28=f+16 | | 56=11x-76x= | | x^2+5x−14=0. | | 14x-5-4x=45 | | 10x-54=5(2x+4) | | 2(1.15x+1.4)=-1.2x+9.8 | | 64=8*g | | -12=6b+12 | | 3(x+1=5(x+3) | | 0.32=0.4e | | w*3=36 | | -x+59=258 | | 10^10−3x=10,000 | | 6x+4+14x+6=130 | | 44+2x=60 | | 60=c*15 |